First Person Account COVID 19 Delirium in a Doctor: When Death Stalks the Mind - Arumi, Antonio; Bulbena-Cabre, Andrea; Bulbena, Antonio (Frontiers in Psychiatry, 2021)
Previous studies reported that 20–30% of COVID-19 patients will develop delirium during the hospitalization, achieving 70% in cases of severe illness. The risks factors and the consequences of delirium are well documented in the literature; however, little is known about the personal experience of delirium. Delirium burden is common and tends to be distressing even after the delirium episode has resolved. Taking this in mind, the present work provides a first-person account of a doctor who acquired COVID 19 bilateral pneumonia and developed delirium. During the course of the delirium, the patient recalled experiences of reality and unreality, complete disorientation, lack of control, strong emotions and intense fear of dying which is consistent with delirium burden and was significantly distressing. We anticipate that delirium burden will be common in COVID patients and family members and clinicians should be aware of this phenomenon in order to evaluate the neuropsychiatric consequences of this condition.